Oceanic island biogeography through the lens of the General Dynamic Model: assessment and prospect - Whittaker, R; Borregaard, M; Amorim, I; Borges, P; Cabral, J; Fernández-Palacios, J; Field, R; Heaney, L; Kreft, H; Matthews, T; Olesen, J; Price, J; et al. (Wiley, 2016)
The general dynamic model of oceanic island biogeography (GDM) has added a new dimension to theoretical island biogeography in recognizing that geological processes are key drivers of the evolutionary processes of diversification and extinction within remote islands. It provides a dynamic and essentially non-equilibrium framework generating novel predictions for emergent diversity properties of oceanic islands and archipelagos. Its publication in 2008 coincided with, and spurred on, renewed attention to the dynamics of remote islands. We review progress, both in testing the GDM’s predictions and in developing and enhancing ecologicalevolutionary understanding of oceanic island systems through the lens of the GDM. In particular, we focus on four main themes: (1) macroecological tests using a space-for-time rationale; (2) extensions of theory to islands following different patterns of ontogeny; (3) the implications of GDM dynamics for lineage diversification and trait evolution; and (4) the potential for downscaling GDM dynamics to local-scale ecological patterns and processes within islands. We also consider the implications of the GDM for understanding patterns of non-native species diversity. We demonstrate the vitality of the field of island biogeography by identifying a range of potentially productive lines for future research.